Analisis Kepemimpinan Transformasional Dan Motivasi Kerja Untuk Meningkatkan Kinerja Guru SMPN Negeri 3 Kedungwaru Tulungagung - Ahmad Saiful; M. Naim Musyafik (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Human resources play a very important role because humans are the driving force of all company activities. Efforts to improve performance are carried out with a well-organized leadership system and motivation to increase employee morale. The purpose of this study was to determine the effect of transformational leadership and work motivation on teacher performance at SMP Negeri 3 Kedungwaru. This study uses a survey method with a questionnaire as a data collection tool. The population in this study were teachers at SMP Negeri 3 Kedungwaru, amounting to 30 people. Samples taken were 30 teachers with census sampling techniques. Data obtained through questionnaires were tested for validity and reliability by using the product moment correlation formula and cronbach's alpha. Data analysis uses multiple regression analysis, F test, t test, and determination coefficient test and is accompanied by classical assumption testing. The results of the study showed that: (1) Transformational leadership had a positive effect on the teacher performance of SMP Negeri 3 Kedungwaru. This is evident from the results of the t test obtaining a tcount of 4.065 and the significance level of 5% (p <0.05) and H1 received. This means that the better transformational leadership is carried out, the teacher's performance will increase. (2) Work motivation has a positive effect on the performance of teachers at SMP Negeri 3 Kedungwaru. This is evident from the results of the t test obtaining a tcount of 2.599 and a significance level of 5% (p <0.05) and H2 received. This means that the higher the employee's work motivation, the more performance will increase. (3) Transformational leadership and work motivation have a positive effect on the teacher performance of SMP Negeri 3 Kedungwaru. This is evident from the results of the F test to obtain an Fcount of 24.893, which received a significance level of 5% (p <0.05) and H3 received. This means that the better transformational leadership is carried out and the higher the work motivation of employees, the more performance will be